2020
DOI: 10.1016/j.nrl.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Modelos experimentales de desmielinización-remielinización

Abstract: Experimental models provide a deeper understanding of the different pathogenic mechanisms involved in multiple sclerosis. Choosing one model or another depends on the specific aims of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 52 publications
0
6
0
4
Order By: Relevance
“…EtBr is a DNA intercalator and its toxicity preferentially impacts astrocytes by restricting their ability to release trophic factors leading to associated OLs to die, along with the affected astrocytes, while largely sparing neurons. The death of these glia in and around the injection site results in localized demyelination (Torre-Fuentes et al, 2020 ). Immunoreactive GFAP + astrocytes are then recruited, but remain confined to the lesion perimeter.…”
Section: Murine Models Of Msmentioning
confidence: 99%
See 1 more Smart Citation
“…EtBr is a DNA intercalator and its toxicity preferentially impacts astrocytes by restricting their ability to release trophic factors leading to associated OLs to die, along with the affected astrocytes, while largely sparing neurons. The death of these glia in and around the injection site results in localized demyelination (Torre-Fuentes et al, 2020 ). Immunoreactive GFAP + astrocytes are then recruited, but remain confined to the lesion perimeter.…”
Section: Murine Models Of Msmentioning
confidence: 99%
“…Interestingly, while demyelination has been described as being T and B cell-independent, CD4- and CD8-deficient mice had significantly reduced remyelination at the injection site compared to controls, indicating T cells may be involved in myelin repair and proper OPC function (Bieber et al, 2003 ). Unlike EtBr and CPZ, lysolecithin is not considered to be fully immune-independent, acting as a chemoattractant to monocytes and initiating a limited focal inflammatory response (Torre-Fuentes et al, 2020 ) and remyelination that is accompanied by significant astrogliosis (Jeffery and Blakemore, 1995 ). While useful, EtBr and lysolecithin are technically demanding models and de- and remyelination is restricted to the site of injection.…”
Section: Murine Models Of Msmentioning
confidence: 99%
“…SFV is an enveloped virus with the capability of entering CNS and subsequently causing myelin damage (Torre-Fuentes et al, 2017).…”
Section: Semliki Forest Virusmentioning
confidence: 99%
“…Hosts usually recover from this initial period and during the following 4 weeks, a chronic phase can be recognized, defined as a neuroparalytic disease with demyelinating inflammatory lesions similar to MS (Houtman & Fleming, 1996;Lane & Buchmeier, 1997;Steinman, 1996;Torre-Fuentes et al, 2017). At this point, MHV titers are below detection limits and T cells and macrophages are considered the main effectors of demyelination (Wu, Dandekar, Pewe, & Perlman, 2000).…”
Section: Mouse Hepatitis Virus (Mhv)mentioning
confidence: 99%
“…EAE is a suitable model, in which animals develop inflammatory-demyelinating diseases spontaneously and cover the specific spectrum of the pathological and immunological features of MS (Lassmann and Bradl, 2017 ). In mice, the EAE-ON model is induced by injection of myelin oligodendrocyte glycoprotein (MOG) peptide-MOG35–55, and clinical EAE scores are graded daily and blindly according to the standard scoring system (Dietrich et al, 2018 ; Locri et al, 2018 ; Torre-Fuentes et al, 2020 ). Our previous results showed that retinal ganglion cells (RGC), in the retina, were most affected by ON (Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%